Phosphorylation of C4 and Non-C4 phosphoenolpyruvate carboxylase from panicum and the kinetic behaviour of phosphorylated and non-phosphorylated PEPC - Dhiya Dalila Zawawi; x
The C4 photosynthesis pathway is more efficient than C3 photosynthesis due to the capability of phosphoenolpyruvate carboxylase (PEPC) that provides a C02 high concentration at Rubisco, thus reducing the photorespiration rate. PEPC is regulated by internal metabolite with malate or aspartate as its inhibitors, and glucose-6-phosphate (G-6-P) as its activator. Besides, PEPC also regulated by reversible phosphorylation by protein kinase known as phosphoenolpyruvate carboxylase kinase (PEPCK), that leads to an activation of the enzyme by G-6-P and decrease the sensitivity to malate or aspartate. PEPCK shows a high specificity towards PEPC and the reaction has been reported to be light controlled, but the details of mechanisms of PEPC phosphorylation are still unknown.